Literacy and development of non-formal education in sub-Saharan Africa: the "reflect" approach inspired by Freire in Mali - (:unkn) unknown (My University, 2022)
Following this historical trajectory, there is the text "Alphabetisation et developpement de L’education non formelle en Afrique subsaharienne: l’approche «reflect» d’inspiration freirienne au Mali", authored by professor Stéphanie Gasse of the Faculty of Education at the University Rouen Normandy, France. It bears witness to twenty years of observations of the situation of access to basic education in sub-Saharan Africa. Literacy and the development of non-formal education in Mali, with emphasis from his first fieldwork with educational NGOs on research – training – actions carried out in the region. For Gasse, the converging factors that define the social, security and health crisis place vulnerable populations within various social experiences of oppression in the sense developed by Freire's theses. It highlights the author in the light of a panorama of complementary, additional or substitutive offers, presented with a view to characterizing the structures that operate in the field of the fight against illiteracy and the right to education and illustrates different models, in a contemporary perspective, from the approach “Reflect” directly inspired by Paulo Freire.
Keywords: African Research